Effects of molarity and solvents on the optical properties of the solutions of tris[4-(5-dicyanomethylidenemethyl-2-thienyl)phenyl]amine (TDCV-TPA) and structural properties of its film - Gündüz, Bayram (Elsevier B.V., 2013)
The surface morphology of the tris[4-(5-dicyanomethylidenemethyl-2-thienyl) phenyl]amine (TDCV-TPA) film was investigated by high performance atomic force microscopy and the surface roughness parameters such as roughness average (sa), root mean square roughness (sq), surface skewness (ssk) and surface kurtosis (sku) of the TDCV-TPA film were obtained. The TDCV-TPA film indicated the low valleys with bumpy surface. The optical properties of the solutions of the small-molecule semiconducting dye TDCV-TPA for different high molarities, lower molarities and different solvents were investigated in detail. The molar extinction coefficient, optical band gap, angle values of refraction of the TDCV-TPA decreased with increasing molarity, while the absorbance at maximum absorption wavelengths, angle of incidence, electric susceptibility, real part values of the optical conductivity of the TDCV-TPA increased with increasing molarity. The maximum molar extinction coefficient (?max) at ?max values (510 and 509 nm) of the solutions of the TDCV-TPA for 0.024 and 0.010 mM were found to be 1.175 × 105 and 1.931 × 105 L mol-1 cm-1, respectively. The maximum mass extinction coefficient (?max) of the solutions of the TDCV-TPA for 0.024 and 0.010 mM were found to be 163.226 and 268.247 L g-1 cm-1, respectively. The optical band gap (E g) values of the TDCV-TPA for 1, 2 and 3 mM were found to be 1.916, 1.898 and 1.892 eV, respectively. The absorption band edge for DCM varied from 1.882 to 1.997 eV, while the absorption band edge for chloroform varied from 1.923 to 2.027 eV. To obtain lower optical band gap of the TDCV-TPA can be prefered DCM solvent. © 2013 Elsevier B.V. All rights reserved.
Keywords: Molar/mass extinction coefficient; Molarity; Optical band gap; Optical parameters; Surface roughness parameters; TDCV-TPA